Repair of Cranial Bone Defects Using rhBMP2 and Submicron Particle of Biphasic Calcium Phosphate Ceramics with Through-Hole. (27th September 2015) - Jeong, Byung-Chul; Choi, Hyuck; Hur, Sung-Woong; Kim, Jung-Woo; Oh, Sin-Hye; Kim, Hyun-Seung; Song, Soo-Chang; Lee, Keun-Bae; Park, Kwang-Bum; Koh, Jeong-Tae
Abstract : Recently a submicron particle of biphasic calcium phosphate ceramic (BCP) with through-hole (donut-shaped BCP (d-BCP)) was developed for improving the osteoconductivity. This study was performed to examine the usefulness of d-BCP for the delivery of osteoinductive rhBMP2 and the effectiveness on cranial bone regeneration. The d-BCP was soaked in rhBMP2 solution and then freeze-dried. Scanning electron microscope (SEM), energy dispersive spectroscopy (EDS), and Raman spectroscopy analyses confirmed that rhBMP2 was well delivered onto the d-BCP surface and the through-hole. The bioactivity of the rhBMP2/d-BCP composite was validated in MC3T3-E1 cells as an in vitro model and in critical-sized cranial defects in C57BL/6 mice. When freeze-dried d-BCPs with rhBMP2 were placed in transwell inserts and suspended above MC3T3-E1, alkaline phosphatase activity and osteoblast-specific gene expression were increased compared to non-rhBMP2-containing d-BCPs. For evaluating in vivo effectiveness, freeze-dried d-BCPs with or without rhBMP2 were implanted into critical-sized cranial defects. Microcomputed tomography and histologic analysis showed that rhBMP2-containing d-BCPs significantly enhanced cranial bone regeneration compared to non-rhBMP2-containing control. These results suggest that a combination of d-BCP and rhBMP2 can accelerate bone regeneration, and this could be used to develop therapeutic strategies in hard tissue healing.